Straying to Success: The Power of Two Stay Two Stray in an Indonesian EFL Classroom - Ichwan; Mudayat (VELES Voices of English Language Education Society, 2024)
Reading comprehension is a foundational skill in English as a Foreign Language (EFL) learning, yet many students, particularly at the primary level, continue to face persistent challenges in developing it effectively. This study investigates the effectiveness of the Two Stay Two Stray (TSTS) cooperative learning technique in enhancing reading comprehension among primary-level EFL learners. Using a pre-experimental one-group pretest-posttest design, the research involved four instructional sessions over four weeks, during which the TSTS technique was implemented. Twenty-eight students participated in the study and completed both pretest and post-test assessments designed to evaluate various aspects of reading comprehension, including identifying main ideas, supporting details, inference skills, and vocabulary interpretation. The data were analyzed using descriptive statistics and a paired samples t-test to determine the significance of the observed learning gains. Results revealed a statistically significant improvement in students’ reading comprehension scores after the intervention, indicating that the TSTS technique positively impacted their reading performance. The study highlights the potential of cooperative learning to promote deeper engagement, peer collaboration, and improved comprehension outcomes in EFL contexts. Findings contribute to the growing body of literature supporting learner-centred instruction and underscore the importance of adopting interactive, evidence-based strategies in primary English language education.